FACTOR INVESTING AND ESG IN THE CORPORATE BOND MARKET BEFORE AND DURING THE COVID-19 CRISIS - BEN SLIMANE, Mohamed; Jean-MARIE DUMAS; Takya SEKINE (Bankers, Markets & Investors, 2021)
The objective of this paper is to illustrate the factor investing space in credit before and during the COVID-19 crisis and is an extension of our prior practitioner analysis on both the new alternative credit factors and the ESG integration in credit. We use monthly credit excess return in the EUR denominated Investment Grade bond universe for regression analysis and factor picking. ESG was making its way to becoming a mainstream factor within the Investment Grade universe and when the COVID-19 stress hit the financial markets, it displayed a “hedge-like” behavior. Better ESG leading to lower cost of capital has been documented previously, however the realization of this feature in a stress environment is worth investors’ attention.